Sistem Informasi Perancangan Aplikasi Les Private Online Berbasis WEB - Naufaldi Rizqi Eka Pradipta; Rizal Fatoni (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This research aims to develop a web-based online private tutoring platform that can support easy access and improve the efficiency of the teaching and learning process. With the rapid advancement of information technology, interest in more flexible learning methods has increased sharply. This application was created to help students find and register for private tutoring according to their preferences, while also opening opportunities for tutors to expand their service reach. The approach used in this research includes identifying user needs, designing the application, and conducting a system trial. The user needs identification process was conducted through surveys and interviews with students and tutors to understand their preferences and the obstacles faced in undergoing the conventional learning process. Based on the analysis, this platform was designed with features that make it easier for students to choose tutors based on subjects, schedules, locations, and teaching ratings given by previous students. In addition, this platform provides an integrated payment system to facilitate transactions between students and tutors. The system trial phase involved a number of users who tested the application directly to provide feedback on the features provided and to ensure smooth use of the application on a small scale. The results of the study indicate that this system is able to strengthen the relationship between students and tutors, and facilitate the management of study schedules and payment systems. Thus, this application is expected to be an effective alternative solution in the world of education, particularly in providing high-quality and accessible private tutoring services. This platform is expected to make the teaching and learning process more flexible and efficient, allowing students to learn anytime and anywhere according to their needs.